STUDY ON SPATIAL DISTRIBUTION OF CORAL REEFS IN LY SON ISLAND USING GIS AND REMOTE SENSING TECHNIQUE - Quang, Nguyen Hao; Thanh, Luong Van; Duan, Ho Dinh (Vietnam Journal of Marine Science and Technology, 2015)
Research and application of GIS and remote sensing technology combined with field survey in coastal areas of Ly Son island, Quang Ngai province had been carried out to establish the distribution map of submarine habitats. Depth-invariant index was used to correct water column’s affects on spectral reflectance of each habitat. The results of satellite - image classification showed that coral reef ecosystems living with coverage of over 25% were quite low in the south and southeast, and a small portion was in the north of the Lon island. In addition, seagrass ecosystems developed quite well with high coverage in the south and the north of Lon island. Overall, mainly common types of sea bed in Ly Son area were dead coral and seagrass. The accuracy assessment after classification showed that the overall accuracy of the satellite - image interpretation process was 94% and the kappa coefficient was 0.93.